Стан лізингових відносин в аграрній сфері Запорізької області - Плаксін, Олег Анатолійович; Плаксин, Олег Анатолиевич; Plaksin, Oleh (Мелітополь: Люкс, 2015)
UK: Досліджено умови функціонування аграрних підприємств. Визначено характер лізингових відносин, визначено потенціал лізингу в реалізації завдань оновлення і модернізації основних засобів підприємств аграрної сфери усіх форм власності, і проаналізовано відношення сільгоспвиробників до лізингу, його проблеми та перспективи в Україні, визначена наявність суб’єктивного фактору та його вплив у повільному просуванні цього виду бізнесу в аграрній сфері. Запропоновано шляхи усунення проблем. EN: The necessity of leasing development in agrarian sphere has been substantiated in the article. Leasing sensitivity to subjective factors has been considered. Specialization of agrarian enterprises in the region has been studied. The ways of problems solving in material and technical provision of agrarian enterprises have been suggested. In the leasing share structure source for material and technical base renovation has been fixed. Influence of leasing awareness on the number of leasing contracts has been determined. Interdependence of leasing and education level as well as time has been determined. Lack of competition at the leasing services market has been noticed. The character of leasing perception depending on the education, organizational and legal forms of factories has been investigated. The reasons of negative attitude to leasing from small-farm owners have been ascertained. Quantity and quality of information on leasing is unsatisfactory. The sources of information about leasing have been determined. The level of landowners eagerness to take part in partnership in the process of leasing has been established. The necessity of change in leasing sellers and agrarian producers was determined. The choice substantiation agrarian enterprises technical base means was defined. It has been found out that there is the lack of interdependence between leasing services and educational level. The author points out the main leasing development restrictive factors in the agrarian sphere: political instability, law changes, the lack of flexibility in leasing sellers’ policy etc. Basic directions for improving leasing servicing quality have been proposed.
Keywords: національна економіка; аграрна сфера; лізингодавець; договір лізингу; лізинг; потенціал